Farmers' Perception and Adaptation Decision of Rice Farming in Facing Climate Change: A Case Study in Trawas Village, Mojokerto, Indonesia - Hasibuan, Amir Fauzan Martua; Sujarwo, Sujarwo; Syafrial, Syafrial (Agro Bali : Agricultural Journal, 2025)
Climate change is a phenomenon of changes in global temperatures, seasons and erratic rainfall that have an impact on human activities, change people's lives, and etc. This research uses a quantitative survey method. The data obtained were analyzed descriptively to obtain an overview of information, sources of information, perceptions and adaptation of farmers and logistic regression to determine the factors that influence farmers' climate change adaptation practices. The results showed that 67% of farmers felt climate change by relying on climate change information sources from newspapers/TV 42%, extension workers 28%, internet 16%, and friends/relatives 14%. Based on farmers' perceptions with a likert scale of 1= unchanged, 2=slightly changed 3=changed a lot, 4=very changed, climate change with many changing categories found in rainfall season (2.76) dry and rainy season (2.64), air temperature (2.63), length of rainy season (2.69), pest and disease attack (2.79), while the length of dry season changed slightly (2.46) with the most impact felt by farmers is the attack of pests and diseases that increase in longer rainy season. These findings imply that farmers, community organizations, and governments must be aware of climate change in order to mitigate the impact of losses on the rice crop agriculture sector. Farmers will benefit tremendously from the farmer adaptation process, group engagement, and government climate policies such as providing drought and flood-climate-resistant cultivars, early warning systems, facilities, and infrastructure.